(untitled) (Manila, Philippines, 1999)
Regional strategies and international instruments to fight corruption, measures to combat and prevent corruption, developing anticorruption strategies.
Keywords: Thái Bình Dương,Corruption,Tham nhũng,Châu Á; Điều kiện kinh tế,Điều kiện kinh tế